Cytomegalovirus Associated Duodenal Ulcer and Duodenitis in a Malnourished Pediatric Patient - Rachel Bernard; Ghanim Aljomah; Emily Klepper; Elizabeth McDonough (Case Reports in Pediatrics)
Cytomegalovirus (CMV) duodenitis is a rare occurrence, especially in pediatric patients. A thirteen-month-old female presented to the Emergency Department for a febrile seizure. She was incidentally admitted for severe malnutrition with an initial workup remarkable for only a slight elevation in her ALT at 48. The patient was found to have an oral aversion requiring nasogastric tube feeds for adequate caloric intake. She continued to fail to gain weight and underwent an EGD that demonstrated a duodenal ulcer. She was consequently started on sucralfate and omeprazole. Post-EGD lab work demonstrated a pronounced increase in AST and ALT. Pathology from the EGD biopsies later demonstrated viral inclusion bodies consistent with CMV duodenitis. Apart from malnutrition, other causes of immune deficiency were eliminated from the differential diagnosis due to negative HIV PCR and normal immunoglobulins. While on antiviral treatment, her viral load of 1080 IU/mL trended to resolution and her liver enzymes normalized. The patient was ultimately discharged home demonstrating adequate weight gain via gastrostomy tube feeds. This case advocates for pediatricians to include immunodeficiency and infectious etiologies in their differential for malnourished patients in order to lead to earlier diagnosis and management of this treatable condition.